2019
DOI: 10.3390/w11010168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods to Estimate Lake-Surface-Water Temperature Using Landsat 7 ETM+ and MODIS Imagery: Case Study of a Large Shallow Subtropical Lake in Southern Brazil

Abstract: Water temperature regulates many processes in lakes; therefore, evaluating it is essential to understand its ecological status and functioning, and to comprehend the impact of climate change. Although few studies assessed the accuracy of individual sensors in estimating lake-surface-water temperature (LSWT), comparative analysis considering different sensors is still needed. This study evaluated the performance of two thermal sensors, MODIS and Landsat 7 ETM+, and used Landsat methods to estimate the SWT of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 69 publications
(167 reference statements)
1
21
0
1
Order By: Relevance
“…This is done, due to the study area comprising of both vegetative and non-vegetative details. Similarly, this was done by Tavares et al [32], Hesslerová et al [34], Kumari et al [35], and Walawender et al [36].…”
Section: Land Surface Temperature (Lst) Calculationmentioning
confidence: 62%
See 1 more Smart Citation
“…This is done, due to the study area comprising of both vegetative and non-vegetative details. Similarly, this was done by Tavares et al [32], Hesslerová et al [34], Kumari et al [35], and Walawender et al [36].…”
Section: Land Surface Temperature (Lst) Calculationmentioning
confidence: 62%
“…In this study, we chose both Landsat thermal bands of Landsat 7 ETM+; namely the low gains band 6 (6L) and high gains band 6 (6H). Band 6L detects areas where surface brightness is high (non-vegetated areas), whereas band 6H detects areas where surface brightness is low (vegetated areas) [32]. A study by Nguemhe Fils et al [33] had used only band 6H as their project was based on a high vegetation area where surface brightness was lower.…”
Section: Land Surface Temperature (Lst) Calculationmentioning
confidence: 99%
“…For this study, Landsat 7 ETM+ dual thermal bands were used; specifically, the low gain band 6 (6L) and high gain band 6 (6H). Band 6L shows areas where the surface brightness is high (non-vegetated areas), whereas band 6H highlights areas where surface brightness is low (vegetated areas) [ 27 , 37 ]. In a study where the investigated area sat in a high vegetation area, Nguemhe Fils et al [ 38 ] used only band 6H because the surface brightness was lower.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain an average, both values of 6H and 6L were added and then divided by '2'. Various studies, such as [37,[39][40][41], previously used this method.…”
Section: Plos Onementioning
confidence: 99%
“…The MOD11A2 product includes two instantaneous observations each day (approximately 11:00 and 21:00 local time), with a spatial resolution of 1 km. Many studies have shown that the MOD11A2 product has good accuracy for individual regions, with mean biases ranging from 0.2 • C to 1.05 • C [12,54,55]. The water surface temperature from the MODIS observations of the skin layer is generally lower than the in situ observation of the mixed layer [56][57][58], because of the cool skin effect [12,59].…”
Section: Modis Lake Surface Temperature Ice Albedo and Snow/ice Cover Ratiomentioning
confidence: 99%